Ethanol (EtOH)‐Related Behaviors in α‐Synuclein Mutant Mice and Association of SNCA SNPs with Anxiety in EtOH‐Dependent Patients. (5th September 2018) - Persyn, Wolfgang; Houchi, Hakim; Papillon, Charles‐Antoine; Martinetti, Margaret; Antol, Johann; Guillaumont, Cyrille; Dervaux, Alain; Naassila, Mickael
Abstract : Background: Data have shown a role of α‐synuclein in anxiety and also in addiction, particularly in alcohol use disorders (AUD). Since the comorbidity between AUD and anxiety is very high and because anxiety is an important factor in ethanol (EtOH) relapse, the aim of the present study was to investigate the role of α‐synuclein in moderating EtOH intake, the anxiolytic effects of EtOH, and EtOH withdrawal–induced anxiety and convulsions in mice. The study aimed to determine whether SNCA variants moderated anxiety in EtOH‐dependent patients. Methods: We analyzed the moderator effect of 3 SNCA Tag‐single nucleotide polymorphisms (Tag‐SNPs) rs356200, rs356219, and rs2119787 on the anxiety symptoms in 128 EtOH‐dependent patients. We used the C57BL/6JOlaHsd Snca mutant mice to assess EtOH intake; sensitivity to the anxiolytic effects of EtOH in a test battery comprising the open field, the light–dark box, and the elevated plus maze; and both anxiety and convulsions induced by EtOH withdrawal. Results: Our results demonstrated a reduction in both EtOH intake and preference and also a lack of sensitivity to the anxiolytic effects of EtOH in α‐synuclein mutant mice. Results on anxiety‐like behavior were mixed, but mutant mice displayed increased anxiety when exposed to a low anxiogenic environment. Mutant mice also displayed an increase in handling‐induced convulsion scores during withdrawal after EtOH inhalation, but did not differ in terms of EtOH withdrawal–induced anxiety. In humans, we found a significant association of the rs356219 SNP with a high level of anxiety (Beck Anxiety Inventory score >15) and the rs356200 SNP with a positive familial history of AUD. Conclusions: Our translational study highlights a significant role of α‐synuclein in components of AUD. Abstract : SNCA gene has been shown to be one of the most important candidate genes of alcohol use disorders. Here we showed that ‐synuclein mutant mice display reduced ethanol intake and preference, reduced sensitivity to the anxiolytic effects of ethanol and increased handling‐induced convulsions during ethanol withdrawal. rs356219 and rs356200 variants of the SNCA gene were respectively associated with anxiety and positive family history of alcoholism in alcohol‐dependent patients.